KOORDINASI ANTAR ORGANISASI PERANGKAT DAERAH DALAM MENANGANI PASCA BENCANA TANAH LONGSOR KOTA SEMARANG - Fadhly Firman Syafrudin; Dyah Lituhayu (Journal of Management and Public Policy, 2026)
The high frequency of landslide disasters occurring in the upper area of Semarang City requires coordinated and integrated post-disaster management. This study aims to analyze the coordination between the Regional Disaster Management Agency (BPBD) of Semarang City and other local government agencies (OPD), as well as to identify the inhibiting factors in the coordination process. This study focuses on inter-agency coordination in post-landslide disaster management within the governmental scope, while previous studies have primarily focused on government collaboration, disaster mitigation, and emergency disaster response. This research employed a descriptive qualitative method with data collection techniques including interviews, observations, literature studies, and documentation. The results show that post-landslide disaster management has been carried out by utilizing information technology, such as WhatsApp Groups and the Lapor Semar platform, to accelerate information exchange. The existence of the Disaster Risk Reduction Forum (FPRB) also serves as an important forum for uniting efforts between volunteers and government agencies. Several coordination barriers were identified, including lengthy bureaucratic procedures in distributing unexpected expenditure funds (BTT), situational coordination patterns, and the absence of routine coordination schedules. The novelty of this study lies in its focus on post-landslide disaster coordination among local government agencies in Semarang City, emphasizing vertical and horizontal coordination patterns within the context of post-disaster rehabilitation and reconstruction. This study concludes that coordination requires stronger functional integration, bureaucratic simplification, disaster training and simulations, and the establishment of routine coordination schedules to improve the effectiveness of post-disaster management.